ANALISIS FAKTOR – FAKTOR YANG MEMPENGARUHI PREFERENSI KONSUMEN DALAM PEMBELIAN PRODUK FOOD AND BEVERAGE DI SHOPEE - Ajeng Kartika Galuh; Minerva Maharani Azzahra (Islamic Economics and finance in Focus, 2023)
The existence of the COVID-19 virus prompted the government to issue an Emergency Community Activities Restrictions Enforcement (PPKM) policy that aimed to suppress positive cases, yet, on the other hand, detrimental to the community since they could not carry out transactions directly to meet their needs. However, the existence of e-commerce can help people to fulfill their needs by making transactions online. Each individual in the community has different preferences in making purchasing decisions. As Muslims, we are obligated to consume halal products, other than that, product quality and prices can also influence consumer preferences in purchasing decisions. Therefore, this study aims to analyze the influence of halal labels, product quality, and product price perceptions on consumer preferences in purchasing food and beverage products at Shopee.  The approach used in this study is a quantitative approach through logistic regression analysis. The results showed that the variables of halal labels and price perceptions significantly affected consumer preferences in purchasing decisions. Meanwhile, the product quality variable has no significant effect on consumer preferences in purchasing decisions.